La fabrique des urbanistes. Une identité professionnelle controversée ? - Laurent Matthey; Christophe Mager (Cybergeo, 2016)
This text explores the professional identity of Swiss urbanists (urban planners-designers and city planners) at a unique moment in the history of the subject: the advent of a new professionalism in the scope of practice. The authors try to understand, in a local context characterised by 1) a mutation in the institutions and tools of urban production; 2) redesigning of the degree programs leading to the title of ‘urbanist’, how the historical players in the profession are organising themselves to defend a concept of professional practice in harmony with their own course of studies – particularly oriented towards the project, considered as an art of graphic representation. The case study examines the Republic and Canton of Geneva in Switzerland, which has served as a laboratory for increasing the flexibility of urbanism; its Institute of Architecture has recently been shut down, leaving the field open for specialists in the social sciences of development to train the professionals in charge of the fabric of urban territory. The authors show how a discourse based on the erosion of professional standards (‘deprofessionalisation’) has been created, mainly by individual participants and not widely relayed by professional associations, who are striving to protect the licence (as the term is used by Everett Hughes) for city-making granted to architects formally recognized as urbanists. The authors draw on materials collected from two surveys, one of them in progress; the first is devoted to the transformations of the professions of urbanism and the second to the new training programs for the trades related to territorial fabric.